New Publications in Forensic Science - Nataliya V. Fetisenkova; Anna A. Ignatyeva (Теория и практика судебной экспертизы)
This section presents translated abstracts of selected papers that appeared in the following periodicals: Journal of Forensic Sciences (JFS), Volume 61, Issues 5 and 6, 2016 (American Academy of Forensic Sciences), published by Wiley (USA), [available online at www.onlinelibrary.wiley.com]; Science & Justice, Volume 56, Issues 3 and 5, 2016 (Journal of the Chartered Society of Forensic Scientists), published by Elsevier Ireland Ltd [contents lists available at: www.sciencedirect.com; journal homepage: www.elsevier.com/locate/scijus]; Problems of Forensic Sciences (PFS), Volumes 103 and 104, 2015, Institute of Forensic Research in Krakow (Poland), [available online at www.forensicscience.pl].